Labor–Management Partnership and Employee Voice: Evidence from the Healthcare Setting. Issue 4 (October 2016) - Avgar, Ariel C.; Sadler, Julie Anna; Clark, Paul; Chung, Wonjoon
Abstract : This paper examines the relationship between labor–management partnership (LMP) and employee voice in the healthcare setting. We argue that the ability of LMP to deliver gains to employees is contingent on the quality of the procedural infrastructure on which it is established. We maintain that the quality of LMP processes influences employee trust in their employer and perceptions of union effectiveness and that these perceptions, in turn, are related to employee patient‐care voice.